The Evolution of Interaction Shape in Differential Susceptibility. Issue 6 (29th December 2016) - Del Giudice, Marco
Abstract : Expectations about the shape of statistical interactions play a crucial role in the study of differential susceptibility and other types of person–environment interplay. These expectations shape methodological guidelines and inform the interpretation of empirical findings; however, their logic has never been explicitly examined. This study is the first systematic exploration of the evolution of interaction shape in differential susceptibility. The model introduced here yields a number of novel insights; for example, interactions in differential susceptibility should usually be asymmetric and likely to be biased toward the prototypical shape of diathesis–stress models. This article also presents an exploratory analysis of interaction shape in recent empirical studies and ends with a discussion of the theoretical and methodological implications of the present findings.